The Effectiveness of Corporate Governance on Profit Quality Improvement in the Transportation Sector of the Indonesia Stock Exchange - Janiko, Pajar; Alhadi, Esya; Lupikawaty, Marieska (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
This research explores the impact of corporate governance mechanisms, specifically institutional and managerial ownership, on the earnings quality of transportation firms listed on the Indonesia Stock Exchange between 2018 and 2022. The study utilized secondary data derived from financial reports, with multiple linear regression analysis executed via SPSS 23. The findings indicate that managerial ownership exerts a significantly positive effect on earnings quality, whereas institutional ownership demonstrates a significantly negative influence. These findings suggest that transportation companies need to enhance communication with institutional shareholders to manage short-term pressures that may lead to earnings manipulation. Additionally, increasing managerial ownership can promote higher earnings quality and sustainable company performance. For investors, this emphasizes the importance of monitoring corporate governance practices and management performance as potential indicators of earnings manipulation. Recommendations for future research include a deeper exploration of corporate governance variables, extending the study period, including more industry sectors, and also employing alternative methods for a more comprehensive evaluation of earnings quality. Overall, this study underscores the crucial role of effective corporate governance in enhancing transparency and accuracy in corporate financial reporting.